First record of two rare Agaricales (Basidiomycota) from Southeastern Brazil - Larissa Trierveiler-Pereira; Amanda Prado-Elias; Juliano M. Baltazar (Rodriguésia)
Abstract The loss of natural forests in Brazil demands an urgent cataloging of species. The Atlantic Forest, one of the many Brazilian ecological domains, is considered a hotspot of biodiversity. Although this domain has the best documented funga among the Brazilian domains, more study is necessary in order to better understand its fungal composition. During our studies in the “Carlos Botelho” State Park (São Paulo, Southeastern Brazil), specimens of two rare species, Panellus olivaceus and Resupinatus porosus, were collected, examined and identified. The first, which grows on bamboo, produces tiny, olivaceus basidiomes (1-4 mm wide) with poroid hymenophore, and broadly ellipsoid, yellowish, amyloid basidiospores. The species is considered rare by the original author and in Brazil there are only records from the state of Paraná (Southern Brazil). Resupinatus porosus is characterized by its palmicolous/lignicolous habitat, small size (0.5-2.5 cm wide), light brown to grayish brown basidiomes, gelatinous context, poroid hymenophore, and globose, hyaline, inamyloid basidiospores. The species was previously only known from the type locality in Puerto Rico and here we report its occurrence in South America for the first time. Description and color photographs are presented for both species.